The influence of perceived usefulness, perceived ease of use and trust on intention reuse of Go-pay - Andre Lorenza Sairaga; Arief Maulana (Universitas Negeri Padang, 2023)
This purpose of this research was to analyze: the effect of perceived usefulness, perceived ease of use and trust on intention reuse of Go-Pay e-wallet in the city of Padang. The method used in this research is quantitative. The population in this research are all people who live in the city of Padang. The sample in this research is 190 people. This research used the Structural Equation Model (SEM) analysis technique using SmartPLS 3.0 software for data analysis. The results of this research show that : (1) perceived usefulness has a significant on intention reuse (2) perceived ease of use has a significant on intention reuse (3) trust has a significant on intention reuse.